KAJIAN FILOSOFI AQIQAH DAN UDHIYAH (PERSPEKIF ALQURAN DAN SUNNAH) - Hj. Nurnaningsih, Hj. Nurnaningsih (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
Aqiqah and Udhiyah which is a keyword in this paper are described by a system of philosophy, using descriptive qualitative method that aims to provide an understanding of all aspects related to the need for its implementation Syarâi and the conditions specified in the legal basis for al quran, Sunnah and ijma Ulama. There are several views about the need for the implementation of Aqiqah and Udhiyah so that in principle it can be said is a guidance Worship categorized in